Effects of different verbal commands on perceptual, affective, and physiological responses during running - Ferreira, Sandro dos Santos; Bomfim Neto, Armando Luiz; Follador, Lucio; Garcia, Erick Doner Santos de Abreu; Andrade, Vinícius Ferreira dos Santos; Silva, Sergio Gregório da (Motriz : Revista de Educação Física. Unesp, 2021)
Abstract Aims: To compare the effects of different verbal commands on the perceptual, affective, and physiological responses during running. Methods: Twenty men who regularly performed aerobic exercise and running (mean age: 30.7±10.1 years; mean VO2max: 55.3 ± 7.1 mL·kg−1·min−1). All subjects completed four exercise sessions: a familiarization trail; three running sessions consisting of a self-selected pace defined by one of the verbal commands: low, moderate, or high. These conditions were counterbalanced. Each running session lasted 20 min. Affective responses (measured by the Feeling Scale and the Felt Arousal Scale) and physiological (measured by the hate rate and treadmill speed) were evaluated during each exercise session. Session RPE (OMNI-RES) was measured 15 min after each exercise session. Results: The perceptual and physiological responses were different for all verbal commands, with the intensity increasing according to the verbal commands given during running (p < 0.01). Affective responses to low and moderate exercise were similar and more pleasant than at high intensities; however, the affective responses to all verbal commands were positive. Conclusion: The results of the present study suggest that verbal commands can be used in running prescriptions. A moderate verbal command can promote greater perceptual and physiological stimuli than a low verbal command, without significant changes in affective responses.